Experimental comparison of the structural, magnetic, electronic, and optical properties of ferromagnetic and paramagnetic polycrystalline Zn1-xCoxO (x=0,0.05,0.1) - Deka, Sasanka; Pasricha, Renu; Joy, Pattayil Alias (Physical Review B, 2006)
Ferromagnetism at room temperature is observed in one case whereas paramagnetism down to 12 K is observed in the second case when polycrystalline Zn1-xCoxO is synthesized under almost identical conditions. Identical x-ray diffraction, optical absorption, and x-ray photoelectron spectroscopy results indicate the incorporation of Co2+ ions in the ZnO lattice in both cases. However, electron diffraction studies show the presence of Co metal impurities in the ferromagnetic samples, indicating that pure Co doped ZnO is not likely to be ferromagnetic.

Thermally assisted semiconductor-like to insulator transition in gold-poly(methyl methacrylate) nanocomposites - Abyaneh, Majid Kazemian; Pasricha, Renu; Gosavi, S. W.; Kulkarni, S. K. (Nanotechnology, 2006)
Gold-polymethylmethacrylate ( PMMA) nanocomposites were fabricated by mixing gold nanoparticles capped with oleylamine in polymethylmethacrylate. The samples were analysed using UV-vis absorption spectroscopy, transmission electron microscopy, small angle x-ray scattering, Fourier transform infrared spectrometry ( FTIR) and x-ray photoelectron spectroscopy ( XPS). Electrical resistivity of nanocomposite samples was measured by a four-probe technique in the 70-300 K range. The nanocomposites showed a transition with an onset at similar to 160-165 K. They exhibited a semiconductor-like conductivity at higher temperatures and nearly temperature independent conductivity at lower temperatures. The interfacial interaction of Au nanoparticles and PMMA polymer is investigated using FTIR and XPS. A ligand-exchange process occurs when capped gold nanoparticles are incorporated in PMMA polymer.

Effect of halogen addition to monolayer protected gold nanoparticles - Singh, Sanjay; Pasricha, Renu; Bhatta, Umananda M.; Satyam, P. V.; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2007)
The effects of N-halosuccinimide and halogen addition to monolayer protected gold nanoparticles (Au NPs) dispersed in organic media are described. Contrary to the expectation that nanoparticles dispersed in organic media are stable against aggregation, N-iodosuccinimide addition induced aggregation of octadecylamine capped gold nanoparticles in chloroform or toluene. It was observed that even KI and CuI addition could bring about the aggregation though they are very sparingly soluble in organic solvents. It was also found that even molecular iodine could bring about the above mentioned aggregation. Interestingly, when CuI is used the aggregated structures readily convert to very thin flat nanostructures upon exposure to an electron beam or UV irradiation. In fact when the aggregation is induced by the addition of KI or N-iodosuccinamide we do not see the flattening of the aggregated structures exemplifying the important role of Cu ions in making these flat structures.

Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Nitrate reductase-mediated synthesis of silver nanoparticles from AgNO3 - Kumar, S. Anil; Abyaneh, Majid Kazemian; Gosavi, S. W.; Kulkarni, Sulabha K.; Pasricha, Renu; Ahmad, Absar; Khan, Mohammad Islam (Biotechnology Letters, 2007)
Synthesis of silver nanoparticles using alpha-NADPH-dependent nitrate reductase and phytochelatin in vitro has been demonstrated for the first time. The silver ions were reduced in the presence of nitrate reductase, leading to the formation of a stable silver hydrosol 10-25 nm diam. and stabilized by the capping peptide. The nanoparticles were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption. These studies will help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: Capping Peptide; enzymatic method; nitrate reductase; silver nanoparticles

Synthesis and LPG sensing properties of nano-sized cadmium oxide - Waghulade, R. B.; Patil, P. P.; Pasricha, Renu (Talanta, 2007)
This paper reports the synthesis and liquid petroleum gas (LPG) sensing properties of nano-sized cadmium oxide (CdO). The nano-sized CdO powder was successfully synthesized by using a chemical co-precipitation method using cadmium acetate and the ammonium hydroxide, as starting materials and water as a carrier. The resulting nano-sized powder was characterized by X-ray diffraction (XRD) measurements and the transmission electron microscopy (TEM). The LPG sensing properties of the synthesized nano-sized CdO were investigated at different operating temperatures and LPG concentrations. It was found that the calcination temperature and the operating temperature significantly affect the sensitivity of the nano-sized CdO powder to the LPG. The sensitivity is found to be maximum when the calcination temperature was 400 degrees C. The sensitivity to 75 ppm of LPG is maximum at an operating temperature 450 degrees C and it was found to be similar to 34 1 %. The response and recovery times were found to be nearly 3-5s and 8-10s, respectively. The synthesized nano-sized CdO powder is able to detect up to 25 ppm for LPG with reasonable sensitivity at an operating temperature 450 degrees C and it can be reliably used to monitor the concentration of LPG over the range (25-75 ppm). The experimental results of the LPG sensing studies reveal that the nano-sized CdO powder synthesized by a simple co-precipitation method is a suitable material for the fabrication of the LPG sensor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical co-precipitation; Gas sensor; LPG; nano-sized CdO

Low temperature synthesis of ZnSe nanoparticles - Deshpande, Aparna; Singh, Shashi B.; Abyaneh, Majid Kazemian; Pasricha, Renu; Kulkarni, S. K. (Materials Letters, 2008)
Synthesis of thioglycerol capped zinc selenide nanoparticles with a relatively narrow size distribution by a simple and inexpensive low temperature (similar to 80 degrees C) wet chemical method is reported here. Main advantage of this method is the use of non-toxic precursors. The size of the nanoparticles can be varied easily by changing the concentration of the capping agent. The extracted nanoparticles remain stable under normal atmospheric conditions and can be redispersed in suitable solvents. The sharp absorption features obtained in the UV-Visible absorption spectra reveal the formation of monodispersed ZnSe nanoparticles. The nanoparticles were characterized using X-ray photoelectron spectroscopy, X-ray diffraction, UV-Visible absorption spectroscopy, photoluminescence and transmission electron microscopy. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanomaterials; Semiconductor; X-ray techniques

New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
National Review and Coordination Meeting on Nanoscience and Nanotechnology, Hyderabad, INDIA, 2007
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Parametric dependence studies on cracking of clay - Pasricha, Kanika; Wad, Uday; Pasricha, Renu; Ogale, Satishchandra (Physica A-Statistical Mechanics and its Applications, 2009)
We have studied the shrinkage-crack patterns formed in the process of drying of clay/water slurries employing simple laboratory experiments. Both isotropic and directional drying was studied. The objective has been to examine the correlation between the solvent, materials parameters and the crack patterns. Attempt is made to fit the observations to specific models. The dynamics of the pattern formation process and the geometric properties of the crack patterns are found to be in conformity with the hydrodynamic model by Lee and Routh [W.P. Lee, A.F. Routh, Langmuir 20 (2004) 9887]. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: clay; Cracks pattern; Hydrodynamic model

Porous anisotropic metal nanostructures through controlled transmetallation across a dialysis membrane - Shukla, Sourabh; Pasricha, Renu; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2009)
Nanostructured metals with hollow interiors are of technological importance due to their unique optoelectronic properties and enhanced surface area. We describe herein, a novel method for the synthesis of anisotropic gold and palladium nanoparticles through a simple galvanic replacement reaction across a semi-permeable dialysis membrane. The control over the reaction kinetics achieved by the presence of membrane enables one to tune the bimetal composition, particle porosity and morphology. Rapid outward diffusion of silver ions generated from the sacrificial silver nanoparticles even at room temperatures prevents the precipitation of high quantities of silver chloride, thereby circumventing the need for product purification. The porous anisotropic nanostructures have potential applications in catalysis, cell imaging and therapeutics.
Keywords: Ag/Pd Nanostructures; Anisotropic Nanoparticles; Dialysis; Galvanic Replacement; Porous nanostructures; Silver Nanotriangles; Silver Nanowires; Transmetallation

Shape and size selective separation of gold nanoclusters by competitive complexation with octadecylamine monolayers at the air-water interface - Pasricha, Renu; Singh, Amit; Sastry, Murali (Journal of Colloid and Interface Science, 2009)
The paper presents a time-dependent study of shape-dependent preferential complexation of gold nanoparticles to the octadecyl amine (ODA) monolayers at the air-water interface. Room temperature reduction of chloroaurate ions using lemon grass leaf extract yields a Mixture of spherical and triangular nanoparticles, which were used for this study. These nanoparticles have a net negative charge on their surface due to the presence of biomolecules from plant extract and thus a strong attractive electrostatic interaction with the positively charged ODA monolayers drives the complexation process. The extent of preferential complexation of the gold nanoparticles to the ODA monolayers is a function of the charge on the particles and the relative mobility of the nanoclusters in the medium. The complexation process has been followed in real time by a host of techniques such as surface pressure-area (pi-A) isotherms, UV-vis-NIR spectroscopy and Brewster angle microscopy. The charge and mobility of the gold nanoparticles was confirmed by measurement of their electrophoretic mobility. Langmuir-Blodgett films of the nanogold-ODA composites have been characterized by UV-vis-NIR spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. These measurements clearly indicate that the cluster mobility and complexation increase with decreasing cluster size. In the competitive complexation process of large and small gold particles, it was observed that some bigger gold particles were also incorporated into the amine matrix even though the cluster mobility is higher for smaller gold particles. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Competitive complexation; gold nanoparticles; Langmuir-Blodgett technique; ODA monolayer

Silver fused conducting fiber formation of Au-Ag core-shell nanoparticles mediated by ascorbic acid - Murugadoss, A.; Kar, Manoranjan; Pasricha, Renu; Chattopadhyay, Arun (Plasmonics, 2009)
In this paper, we report the spontaneous formation of fibrous structures consisting of assemblies of Au-Ag core-shell nanoparticles (NPs) from a solution consisting of Au-Ag core-shell NPs and l-ascorbic acid (AA). AA acted both as the reducing agent for the generation of NPs and also as the mediator for the formation of fibers. The process of fiber formation involved three steps-reduction of HAuCl(4) to Au NPs by AA, subsequent formation of Au-Ag core-shell NPs after addition of AgNO(3), and spontaneous formation of fibers from the mixtures in water. It took typically about 30 days to form complete fibers that are of lengths of several hundred micrometers to millimeters, although nanofibers started forming from the first day of solution preparation. The width of each of these fibers was typically about 1-4 A mu m with length of each segment of fiber bundle, on the order of 40 A mu m. Formation of fibers was also observed in absence of AgNO(3). These fibers consisted of Au NPs and polymer of AA degradation products and were not electrically conducting. Also, low concentrations of AgNO(3) produced fibers with low electrical conductivity. However, it was observed that increase in the amount of AgNO(3) leads to the formation of fibers that were electrically conducting with conductivity values in the range of metallic conductivity. Spectroscopic and electron microscopic investigations were carried out to establish the formation of fibers. The details of fiber formation mechanism under different conditions and electrical conductivities of the fibers are discussed in the article.
Keywords: Ascorbic acid; core-shell; Fiber; Gold; Nanoparticles; Silver

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles